Analisis Kebutuhan dan Rancangan Program Digital Upskilling bagi Fresh Graduate di Provinsi Gorontalo - Andi Yusniar Mendo; Syamsul B. Biki; Mentari Rizki Sawitri Pilomonu; Mohammad Dimas Suronoto; Arif Ramadhan Humulungo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Fresh graduates in Gorontalo Province face a significant skills gap when entering the digital economy, necessitating effective digital-based training. This research aims to design an online training program that can bridge this gap using the Theory of Planned Behavior as a theoretical framework. The research method involves descriptive statistical analysis of survey data from 40 fresh graduates, as well as semi-structured thematic interviews to explore specific needs in training design. The results indicate that positive attitudes, subjective norms, and perceived behavioral control significantly influence the intention to participate in training. The training prototype developed through Figma received positive feedback, although it requires further refinement. The novelty of this research lies in the application of the Theory of Planned Behavior in the context of online training for fresh graduates in developing regions. The implications of these findings highlight the need for a segmented approach in training program design, integration of collaborative elements, and the provision of industry-recognized certification to enhance the employability of new graduates in the digital era